2014
DOI: 10.18632/oncotarget.2176
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of radioresistance in docetaxel-resistant human lung adenocarcinoma cells is linked with dysregulation of miR-451/c-Myc-survivin/rad-51 signaling

Abstract: Chemoresistant tumors usually fail to respond to radiotherapy. However, the mechanisms involved in chemo- and radiotherapy cross resistance are not fully understood. Previously, we have identified microRNA (miR)-451 as a tumor suppressor in lung adenocarcinoma (LAD). However, whether miR-451 plays critical roles in chemo- and radiotherapy cross resistance in LAD is unclear. Here, we established two docetaxel-resistant LAD cell models (SPC-A1/DTX and H1299/DTX), and showed that miR-451 was significantly downreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 46 publications
4
41
0
Order By: Relevance
“…8,9 The present study investigated the roles of miR320a in the proliferation of lung cancer cells, and found that overexpression of miR-320a enhanced the apoptosis of lung adenocarcinoma cells induced by irradiation in vitro and in vivo. Moreover, miR-320a significantly inhibited lung adenocarcinoma cell proliferation and migration by directly regulating STAT3 signals, which was supported by zhao et al, who found that miR-320a plays a critical role in invasion and metastasis of colorectal cancer by regulating Rac1 gene.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…8,9 The present study investigated the roles of miR320a in the proliferation of lung cancer cells, and found that overexpression of miR-320a enhanced the apoptosis of lung adenocarcinoma cells induced by irradiation in vitro and in vivo. Moreover, miR-320a significantly inhibited lung adenocarcinoma cell proliferation and migration by directly regulating STAT3 signals, which was supported by zhao et al, who found that miR-320a plays a critical role in invasion and metastasis of colorectal cancer by regulating Rac1 gene.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, miR-451 can promote radioresistance of cancer cell apoptosis by directly targeting c-Myc. 9 MiR-320a is reported to be deregulated in many malignancy types. Recent studies indicated miR-320a inhibited gastric cancer cell proliferation by downregulating FoxM1 10 and suppressed cancer metastasis by directly targeting metadherin.…”
Section: Introductionmentioning
confidence: 99%
“…miR-451 in this study following qPCR validation demonstrated a significant change in exosome derived from chemoresistance PCa cells as compared to their parental cells. In contrast, miR-451 was downregulated in docetaxelresistant lung adenocarcinoma cells (22). However, miR-451 was upregulated in multidrug-resistant (MDR) human ovarian cancer cell line (A2780DX5) and human cervix carcinoma cell line (KB-3-1), compared with their parental lines.…”
Section: Discussionmentioning
confidence: 96%
“…MiR-145 and miR-224 are reported to confer the chemoresistance of lung adenocarcinoma cells to cisplatin (CDDP) via delaying the progression of the cell cycle from G1 to S phase [13,14]. In addition, miR-650 has been shown as a potential target for chemosensitizing lung adenocarcinoma cells to DTX and of interest, miR-451 play a role in both DTX or CDDP resistance and radioresistance [15,16]. These results clearly suggest that dysregulation of miRNAs is associated with the resistance of lung cancer to anti-cancer therapies have been reported.…”
Section: Lncrnas Biogenesis and Gene Expressionmentioning
confidence: 99%